The legal basis for the right to the city (a comparative study) - عبدالله, فراس عبدالمنعم; حيدر, حيان ابراهيم (Journal of Legal Sciences, 2021)
The issue of human rights occupies great importance on the academia as well as in the reality, especially after the spread of ideas related to these rights on one hand and the large number of violations they are exposed to on the other hand, which makes it necessary to develop fundamental solutions to the remove the obstacles of implementing human rights.      In this research entitled (The Legal Basis of the Right to the City: A Comparative Study) we dealt with a new concept of human rights and discussed the basis upon which it is based in international charters, constitutions and domestic laws.